Diagnosing sexually transmitted infections in resource‐constrained settings: challenges and ways forward - Wi, Teodora EC; Ndowa, Francis J; Ferreyra, Cecilia; Kelly‐Cirino, Cassandra; Taylor, Melanie M; Toskin, Igor; Kiarie, James; Santesso, Nancy; Unemo, Magnus (Journal of the International AIDS Society, 2019)
Introduction Sexually transmitted infections (STIs) remain prevalent and are increasing in several populations. Appropriate STI diagnosis is crucial to prevent the transmission and sequelae of untreated infection. We reviewed the diagnostic accuracy of syndromic case management and existing point‐of‐care tests (POCTs), including those in the pipeline, to diagnose STIs in resource‐constrained settings. Methods We prioritized updating the systematic review and meta‐analysis of the diagnostic accuracy of vaginal discharge from 2001 to 2015 to include studies until 2018. We calculated the absolute effects of different vaginal flowcharts and the diagnostic performance of POCTs on important outcomes. We searched the peer‐reviewed literature for previously conducted systematic reviews and articles from 1990 to 2018 on the diagnostic accuracy of syndromic management of vaginal and urethral discharge, genital ulcer and anorectal infections. We conducted literature reviews from 2000 to 2018 on the existing POCTs and those in the pipeline. Results and discussions The diagnostic accuracy of urethral discharge and genital ulcer disease syndromes is relatively adequate. Asymptomatic Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) infections limit the use of vaginal discharge and anorectal syndromes. The pooled diagnostic accuracy of vaginal syndromic case management for CT/NG is low, resulting in high numbers of overtreatment and missed treatment. The absolute effect of POCTs was reduced overtreatment and missed treatment. Findings of the reviews on syndromic case management underscored the need for low‐cost and accurate POCTs for the identification, first, of CT/NG, and, second, of Mycoplasma genitalium (MG) and Trichomonas vaginalis (TV) and NG and MG resistance/susceptibility testing. Near‐patient POCT molecular assays for CT/NG/TV are commercially available. The prices of these POCTs remain the barrier for uptake in resource‐constrained settings. This is driving the development of lower cost solutions. Conclusions The WHO syndromic case management guidelines should be updated to raise the quality of STI management through the integration of laboratory tests. STI screening strategies are needed to address asymptomatic STIs. POCTs that are accurate, rapid, simple and affordable are urgently needed in resource‐constrained settings to support the uptake of aetiological diagnosis and treatment.